تفعيل المنشور الوزاري رقم242 بهدف اعداد المشروع المدرسي والمهني لمرافقة تلاميذ رابعة متوسط - بن عبد القادر، أشواق, خلافي، مريم (جامعة الوادي university of Eloued, 2020)
الملخص: تهدف الدراسة الحالية إلى تفعيل المنشور الوزاري رقم242 من خلال بناء مشـــــــــــروع مرافقة لتلاميذ سنة رابعة متوسط، وقد جاءت الدراسة الحالية للإجابة عن التساؤلات التالية: "هل مرافقة تلاميذ سنة الرابعة متوسط يمكنهم من بناء مشروعهم المدرسي والمهني؟" "إذا ما تم تفعيل المنشور الوزاري رقم 242 بطريقة صحيحة يمكن للجنة الإرشاد والمتابعة من مرافقة التلاميذ من خلال وضع خطة مكتوبة لبناء مشروعهم المدرسي والمهني؟" وتنص فرضية الدراسة على أنه: نتوقع من خلال مشروع المرافقة المساهمة بقدر كبير في إنجاح المشروع المدرسي والمهني. ولقد تم الاكتفاء بالدارسة الاستطلاعية وتعذر إجراء الدراسة الأساسية بسب ظروف جائحة كرونا، حيث اعتمدت الدراسة الحالية على منهج التجريبي ذو التصميم الواحد وقياس قبلي وبعدي وتكونت الدراسة من 10 تلاميذ من السنة الرابعة متوسط، بمتوسط سلطاني علي، أما الأدوات المستخدمة في هذه الدراسة هي: استبيان لقياس المشروع الشخصي، مشروع مرافقة للتلميذ. ومن الأساليب المستخدمة للتحقق من أهداف الدراسة اختبار"ت" لدلالة بين الفروق القياس القبلي والبعدي. Résumé : انجلزية The current study aims to activate Ministerial Circular No. 242 by building an escort project for fourth-year students، average. The current study came to answer the following questions: Is accompanying fourth-year students an average of them able to build their school and vocational project? "If Ministerial Circular No. 242 is activated، can the Guidance and Follow-up Committee accompany students by developing a written plan to build their school and vocational project?" The hypothesis of the study states that: We expect، through the accompaniment project، to contribute significantly to the success of the school and vocational project The exploratory study was satisfied and it was not possible to conduct the basic study due to the circumstances of the Corona pandemic، as the current study relied on the one-design experimental approach and pre- and post-measurement and the study consisted of 10 pupils of the fourth year average، with an average of Sultani Ali، and the tools used in This study is: a questionnaire to measure the personal project، the project of accompanying the student. One of the methods used to verify the aims of the study is the "T" test for an indication between the differences، pre and post measureme
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: المشروع الدراسي المهني; Projet d'étude professionnelle; Professional study project